MENINGKATKAN KEMAMPUAN MENULIS TEKS PARAGRAF DESKRIPSI MELALUI METODE MIND MAPPING SISWA KELAS VII SMP NEGERI 11 KOTA TERNATE - Ati, Sarmina; Nurbaya, Nurbaya; Samad, Sartika; Barady, Nursafa (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The purpose of the study was to analyze and describe the learning process to improve the ability to write descriptive paragraph texts through the mind mapping method of class VII students of SMP Negeri 11 Kota Ternate. In collecting data, researchers used observation, test, interview, and documentation techniques. This study uses the Classroom Action Research (CAR) type through qualitative and quantitative analysis methods. The results of the study indicate that the use of the mind mapping method through the Student Worksheet (LKS) media can improve writing skills in class VII students of SMP Negeri 11 Kota Ternate. This success can be seen from the comparison of the pre-cycle to cycle I (good qualification level) and from cycle I to cycle II (very good qualification level).